Profil Pasien Perforasi Gaster di RSUD Kolonel Abundjani Bangko pada Tahun 2020 - Shinta Qorina (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Gastric perforation is one of the serious complications caused by a peptic ulcer, with the appearance of symptoms in the form of an acute abdomen that requires immediate treatment. Approximately 2 to 3% of all ulcers perforate which usually occurs in the anterior wall of the duodenum or stomach. Objective. To determine the profile of patients with gastric perforation due to peptic ulcer at RSUD Kolonel Abundjani Bangko. Method. This is descriptive study with a retrospective total sampling method. The target population is patients with a diagnosis of gastric perforation due to peptic ulcers in the period January-December 2020. Result. Total patients with gastric perforation in RSUD Kolonel Abundjani Bangko for the January-December 2020 period totaled 14 people. Male patients were more than female (64.3% vs. 35.7%), the age range of 50-59 years was slightly higher than patients aged over 60 years (50% vs. 42.9%). There was no difference in the number of patients who had and did not have a history of taking NSAIDs. The location of the pre-pyloric perforation (50%) was more common than in the major curvature (14.29), minor (21.43%), and corpus (14.29%). The diameter of the perforation was most commonly found 0.5-1 cm (85.71%) Total deaths were 3 out of 14 people (21.43%). Conclusion. There are more male patients with gastric perforation than female, and the age range of 50-59 years is more common. The location of the perforation was found mostly in the pre-pylorus, and the majority had a perforation diameter of 0.5-1 cm. The mortality rate was reported as 21.43%